2017
DOI: 10.1038/s41598-017-04005-z
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear accumulation of symplekin promotes cellular proliferation and dedifferentiation in an ERK1/2-dependent manner

Abstract: Symplekin is a multifunctional protein that localizes to both tight junctions and the nucleus in polarized epithelial cells, with confirmed roles in mRNA maturation, transcriptional modulation and tight-junction assembly. However, the mechanisms governing its subcellular distribution and related functions remain unclear. In this study, we found that symplekin primarily localizes to the nuclei of cultured dedifferentiated colorectal cancer cells, and nuclear symplekin showed higher phosphorylation and binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Previous reports have shown that nuclear Sympk could interact with transcription factors such as ZONAB and HSF1 [33,34]. Moreover, the nuclear portion of Sympk is required for cell cycle-related gene regulation and β-catenin activation, and enhances proliferation and de-differentiation in colorectal cancer cells [17,18]. In addition, we found that Sympk interacted directly with core pluripotency transcription factors including Oct4, Nanog, and Sox2, in mESCs.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Previous reports have shown that nuclear Sympk could interact with transcription factors such as ZONAB and HSF1 [33,34]. Moreover, the nuclear portion of Sympk is required for cell cycle-related gene regulation and β-catenin activation, and enhances proliferation and de-differentiation in colorectal cancer cells [17,18]. In addition, we found that Sympk interacted directly with core pluripotency transcription factors including Oct4, Nanog, and Sox2, in mESCs.…”
Section: Discussionsupporting
confidence: 53%
“…Post‐translational modifications (PTMs) including sumoylation and phosphorylation, are essential for the function of Sympk in the regulation of cell growth and viability in different tumor cells . Since PTMs are key regulatory process for protein stability, activation, interaction, and cellular localization, we speculate that the post‐translational modification of Sympk is also important for its proper functioning in mESCs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The protein is localized to tight junctions and the nucleus and is involved in transcriptional modulation and mRNA maturation as well as tight junction assembly. Interestingly, phosphorylation of SYMPK T1257 promotes nuclear localization of symplekin and interaction with YBX3, which enhances cell proliferation and differentiation (Zhang et al , 2017). Hyperphosphorylation of FOXO3 has been implicated with myofibroblasts in idiopathic pulmonary fibrosis (Al-Tamari et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrate that CD44v6 crosslinking, besides contributing to NOTCH1 transcription, promotes β -catenin-independent NOTCH and Nanog nuclear translocation. Activation of these transcription factors might be supported by CD44v6-associated MYH3 (Myosin-3) and YBX3 (Y-box-binding protein 3), which can contribute to EMT induction [14, 5961]. Via its linkage to ERM proteins CD44 fosters cytosolic signaling molecule activation and cytoskeleton reorganization [62, 63].…”
Section: Discussionmentioning
confidence: 99%